Virologic response and haematologic toxicity of boceprevir- and telaprevir-containing regimens in actual clinical settings - Butt, A. A. (J Viral Hepat, 2014)
Effectiveness, safety and tolerability of boceprevir (BOC) and telaprevir (TPV) in actual clinical settings remain unknown. We determined rates of sustained virologic response (SVR) and haematologic adverse effects among persons treated with BOC- or TPV-containing regimens, compared with pegylated interferon/ribavirin (PEG/RBV). Using an established cohort of hepatitis C virus (HCV)-infected persons, Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES), we identified those treated with a BOC- or TPV-containing regimen and HCV genotype 1-infected controls treated with PEG/RBV. We excluded those with HIV co-infection and missing HCV RNA values to determine SVR. Primary endpoints were SVR (undetectable HCV RNA ≥12 weeks after treatment completion) and haematologic toxicity (grade 3/4 anaemia, neutropenia and thrombocytopenia). We evaluated 2288 persons on BOC-, 409 on TPV-containing regimen and 6308 on PEG/RBV. Among these groups, respectively, 31%, 43% and 9% were treatment-experienced; 17%, 37% and 14% had baseline cirrhosis; 63%, 54% and 48% were genotype 1a. SVR rates among noncirrhotics were as follows: treatment naïve: 65% (BOC), 67% (TPV) and 31% (PEG/RBV); treatment experienced: 57% (BOC), 54% (TPV) and 13% (PEG/RBV); (P-value not significant for BOC vs TPV; P < 0.0001 for BOC or TPV vs PEG/RBV). Haematologic toxicities among BOC-, TPV- and PEG/RBV-treated groups were as follows: grade 3/4 anaemia 7%, 11% and 3%; grade 4 thrombocytopenia 2.2%, 5.4% and 1.7%; grade 4 neutropenia 8.2%, 5.6% and 3.4%. SVR rates are higher and closer to those reported in pivotal clinical trials among BOC- and TPV-treated persons compared with PEG/RBV-treated persons. Haematologic adverse events are frequent, but severe toxicity is uncommon.